PENDAMPINGAN PENYUSUNAN ANGGARAN BERBASIS KINERJA SMK TRIATMA JAYA - I Ketut Yudana Adi; Kukuh Rian Setiawan; Ida Ketut Kusumawijaya (Universitas Triatma Mulya, 2022)
This community service is carried out in collaboration with Triatma Jaya High School in the context of assisting in the preparation of performance-based budgets. The aim is to provide school administrators with the ability to prepare performance-based budgets and improve the quality of their financial reporting. This activity was attended by three units of SMK, including Triatma Jaya Badung Vocational School, Tabanan Triatma Jaya Vocational School and also Triatma Jaya Singaraja Vocational School which in its implementation were represented by three people each consisting of the Principal, Deputy Head and also the school treasurer. The method used in the community service program uses the RAD (Rapid Application Development) method, which is a method that prioritizes partner involvement in the use of a series of systems, where the series functions to create a more effective prototype. After the dedication, partners understand and understand more about performance-based budgeting and excel-based financial management. this can be seen from the results of the pretest an average score of 60 and after training and mentoring the pastest score is 90.